2013
DOI: 10.15625/0866-7160/v35n1.2933
|View full text |Cite
|
Sign up to set email alerts
|

A new species of genus Acheilognathus, Bleeker, 1895 from the Tien Yen river, Vietnam

Abstract: TÓM TẮT: Bài báo công bố một loài cá mới, cá thè be sọc lớn Acheilognathus nguyenvanhaoi sp. n., loài mới được mô tả dựa vào mẫu thu được từ sông Tiên Yên, tỉnh Quảng Ninh, Bắc Việt Nam. Loài mới khác với các loài còn lại ở những đặc điểm: có 1 sọc dọc, to đều, đen đậm ở mỗi bên thân chạy từ mút mõm đến mút các tia giữa vây đuôi thay vì cao nhất cũng chỉ từ sau nắp mang tới gốc vây đuôi, không to đều; công thức răng hầu (5.1-0.5 thay vì 5-5); số tia gai vây lưng và vây hậu môn (III-IV thay vì III) và số vảy tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…For instance, Arai and Akai (1988) used Acheiloghnathus macropterus; whereas Hwang et al (2014) identified the species Acanthorhodeus. However, more recent studies (Duc et al, 2013;Li and Arai, 2010;Yang, Q. et al, 2010Yang, Q. et al, , 2011 generally agree in recognizing the ''three genera scenario'' (Arai and Akai, 1988). Diagnoses of the genera include characters related to karyotypes, color patterns on dorsal fins, and features of the lateralis system.…”
Section: Taxonomymentioning
confidence: 91%
“…For instance, Arai and Akai (1988) used Acheiloghnathus macropterus; whereas Hwang et al (2014) identified the species Acanthorhodeus. However, more recent studies (Duc et al, 2013;Li and Arai, 2010;Yang, Q. et al, 2010Yang, Q. et al, , 2011 generally agree in recognizing the ''three genera scenario'' (Arai and Akai, 1988). Diagnoses of the genera include characters related to karyotypes, color patterns on dorsal fins, and features of the lateralis system.…”
Section: Taxonomymentioning
confidence: 91%